INTERACTIVE LECTURES: A PERSPECTIVE OF STUDENTS AND LECTURERS - Rehman, Rehana; Afzal, Kamran; Kamran, Ambreen (Journal of Postgraduate Medical Institute, 2013)
Objective: To evaluate usefulness of lectures in learning of basic science subjects by students andlecturers. Methodology: It was a survey carried out in Bahria University Medical & Dental College after completionof six modules of teaching in Basic Sciences from January 2009 till December 2010. Response onusefulness of interactive lectures (IL) was acquired by a questionnaire designed separately for students andlecturers. The data was interpreted by soft ware "Statistical Software for Social sciences" (SPSS) version15. Results: The perception of 97 students and 15 lecturers indicated usefulness of IL in better understandingof subject content. Majority of lecturers (93%) were convinced with its role in concept visualization. Theywere however not convinced with its role in persistence of interest and student's interaction (33%).Majorityof students (84%) were satisfied with delivery of content (p<0.005), 89% understood structural andfunctional relationship by the teaching methodology however felt need of its improvement in terms ofrelevance of knowledge in applied sciences. Conclusion: The lecturers and students agreed upon usefulness of IL and its continuation as part of corecurriculum in teaching of basic science subjects.